Boardthink: Exploring the discourses and mind-sets of directors. (14th August 2017) - Carroll, Brigid; Ingley, Coral; Inkson, Kerr
Abstract: In a context of institutionalized regulation and academic framing determined by agency theory, we note paradoxes in board governance literature and practice. These paradoxes concern boards' conflicting roles of monitoring/control, and innovation/strategy-making. We explore directors' mind-sets about governance on which their resolution of paradoxes and their decisions and actions will be based. We do this by applying discourse analysis to the transcripts of 60 semistructured interviews conducted with New Zealand directors who described and evaluated their experience of board governance. We identify and discuss their various discourses, which we label discourses of conformance, of deliberation, of enterprise and of bounded innovation. We note the homogeneity of discourses across different organization types, the dominance of conformance, the nonresolution of paradoxes, and the likely effects in inhibiting board strategy-making and contribution to innovation. We recommend attention by boards to their mind-sets and processes, and the development of generativity.